Anatomical study of the three-dimensional structure of a supercharged cold eddy generated in the Kuroshio Extension - Zhang, Xinyu; Zheng, Hua; Zhu, Xiao-Hua; Zhao, Ruixiang; Xiao, Cong; Wang, Min; Chen, Juntian (Frontiers in Marine Science, 2022)
The three-dimensional structure of a supercharged cold eddy, which showed strong temperature anomaly, was continuously investigated for 83 days based on current- and pressure-equipped inverted echo sounder observations in the Kuroshio Extension region. The eddy was generated on December 9, 2004, shed from the Kuroshio approximately 30 days later, and moved out of the observation area on March 1, 2005. During the stable period, the eddy had a radius of approximately 60–80 km, a depth of approximately 3,000 m, and a westward speed of 7.4 km/d. The maximum temperature anomaly in the eddy center reached -9.1 °C at 360 dbar, whereas the minimum (maximum) salinity anomaly reached -0.68 (0.20) psu at 340 (780) dbar. Under the stream function coordinate, the kinetic energy of the eddy first increased and then decreased from the center to boundary, whereas the vorticity decreased overall. Energy budget analysis showed that eddy energy mainly originated from the Kuroshio during eddy formation by advection, whereas the baroclinic conversion (BC) and barotropic conversion (BT) played a dissipative role. After the eddy had been completely separated from the Kuroshio, the mean flow energy was transferred to eddy energy through BC and BT, which further enhanced eddy potential energy and eddy kinetic energy.